Literature Review: Pemahaman Konsep Siswa dalam Pembelajaran Kimia - Fathonah, Euis; Hidayati, Aenil; Saputra, Setya; Suhaela, Haya (Universitas Papua, Manokwari, Indonesia, 2024)
Understanding concepts in chemistry subjects is crucial, as a lack of understanding can lead to misconceptions. This research aims to analyze existing research on understanding chemical concepts, thereby leveraging the opportunity to conduct further research on chemistry comprehension. This study employs a literature review method based on a variety of articles that discuss understanding concepts. The analysis of articles on conceptual understanding reveals that the years of article publication range from 2017 to 2024, with no journal publications in 2020. The quantitative method is the most commonly used research method, with class XI students making up the majority of the subjects. Acids and bases are a common chemistry topic in research, and the T test is the most common data analysis method. We've concluded that the majority of articles appeared in 2019 and 2021, quantitative research is the most prevalent type, and class XI students make up the majority of research subjects. The most frequently used data analysis in acid-base research is the T test.